2020
DOI: 10.1002/pat.4993
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Fluorescence Emission of CdSe Quantum Dots Based on the Surface Ligand Exchange with MAA

Abstract: Cadmium selenide (CdSe) quantum dots (QDs) is a promising semiconductor and fluorescence nanocrystal with quantum size effect. To address the problem of fluorescence emission during the process of the ligand transformation of colloidal cluster CdSe QDs from nonpolar organic solvents to polar inorganic aqueous solutions, the surface ligand exchange with mercapto acetic acid (MAA) was proposed. It was attributed to the Cd‐O bond breaking and the Cd‐S bond formation. The intensity and wavelength of fluorescence e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Obviously, it confirmed a defect-free single crystallinity with intrinsic lattice spacings of 2.2, 3.3, and 3.5 Å, corresponding to the (220), (311), and (111) crystal planes of the CdSe microstructure, respectively. 22 It was demonstrated that the crystal structure of the CdSe QDs was in agreement with that of the powders, which had no observable change in the preparation process. The corresponding fast Fourier transform (FFT) image (insert of Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Obviously, it confirmed a defect-free single crystallinity with intrinsic lattice spacings of 2.2, 3.3, and 3.5 Å, corresponding to the (220), (311), and (111) crystal planes of the CdSe microstructure, respectively. 22 It was demonstrated that the crystal structure of the CdSe QDs was in agreement with that of the powders, which had no observable change in the preparation process. The corresponding fast Fourier transform (FFT) image (insert of Fig.…”
Section: Resultsmentioning
confidence: 76%
“…High-resolution transmission electron microscopy (HRTEM) images were also collected to further observe the microstructure of CdSe QDs, and the images could be more distinctly reflected in Fig.1cand Fig.S2 (ESI †). Obviously, it confirmed a defect-free single crystallinity with intrinsic lattice spacings of 2.2, 3.3, and 3.5 Å, corresponding to the (220), (311), and (111) crystal planes of the CdSe microstructure, respectively 22. It was demonstrated that the crystal structure of the CdSe QDs was in agreement with that of the powders, which had no observable change in the preparation process.…”
mentioning
confidence: 60%
“…For QDs with a fixed size, ligands and other reagent species can also affect their emission properties. [72] When exposed to light, an intensity change or wavelength shift can occur, which is attributed to photoactivation, photoelectrification, or photoneutralization. [73][74][75] The energy transfer process can also be utilized to modulate the emission of QDs by constructing a QD-dye system.…”
Section: Luminescence Modulationmentioning
confidence: 99%
“…[84] By using a rational design, the performance of QDs can be improved. [72,133] As an example, alkyl phosphate (TDPA)-coated CsPbBr 3 QD powders were developed, which retained high photoluminescence quantum yield (PLQY, 68%) and narrow band emission (FHWM ≈22 nm), as well as high stability in water and high-temperature atmospheres. [106] The alkyl phosphate matrix prevents agglomeration and fluorescence quenching, leading to a high PLQY.…”
Section: (11 Of 23)mentioning
confidence: 99%
“…The process of organic–inorganic ligand exchange works by way of electron transfer; Cd–O scission and Cd–S formation were involved. Band edge emission was monitored and the maximum red shift found in this case was 28 nm [ 134 ].…”
Section: Selenium In Physics Surfaces and Nanoscience With Regarmentioning
confidence: 99%